The influence of learning value on learning management system use: An extension of UTAUT2 - Ain, N.; Kaur, Kiran; Waheed, M. (SAGE Publications, 2016)
In this study the perceived value construct of the Unified Theory of Acceptance and Use of Technology (UTAUT2) is investigated in the context of a learning management system (LMS), in which the construct is redefined from its original price value conceptualization. It was found that many researchers simply ignore the price value construct when applying the UTAUT2 model in technology use studies in the educational context. This study extends the UTAUT2 framework by integrating the learning value construct and provides fresh insight about predictors of students’ intentions towards LMS and its use. A quantitative research approach was employed by utilizing a closed-ended questionnaire to collect data from Malaysian university students who were users of LMS. Probability proportional stratified sampling was employed to select an appropriate sample. The results indicated a good measurement and structural model fit and suggested the significant influence of performance expectancy, social influence and learning value on students’ intention towards LMS and also confirmed the influence of facilitating conditions and behavioral intention on LMS use. The extended UTAUT2 framework helps in understanding students’ perceived value in the LMS context. Furthermore, this study will help institutions to consider the factors for successful implementation of an LMS in an academic setting.